Scientific and Theoretical Foundations of Agricultural Geography - Radjabov F.T (Zien Journals, 2022)
The article analyzes the scientific and theoretical foundations of agricultural geography. It is covered about the research and main ideas of scientists in the field of agrogeography
Keywords: geography; agriculture; economic space; specialty